Aplicación del programa educativo Rescatando valores para la formacionética de los alumnos del 2º grado del nivel secundario de la I.E. Santo Domingo de Guzmán del Distrito de Chicama, 2017 - Huallán Ramírez, Santos Jesús (2018)
ABSTRACT The general objective of this research was to determine the extent to which the application of the educational program "Rescuing Values" contributes to the ethical training of 2nd grade students at the secondary level of the I.E. Santo Domingo de Guzmán of the district of Chicama, 2017. The research design used was quasi-experimental and we worked with a sample of 60 students, 30 belonged to the experimental group and 30 to the control group. The educational program "Rescuing Values" was aimed at strengthening the values of solidarity, respect, justice and freedom as part of the ethical education of students. It was concluded that the educational program "Rescues Values" contributes significantly to the ethical training of the 2nd grade students of the secondary level of the I.E. Santo Domingo de Guzmán of the district of Chicama, 2017.